Portraying Mental Illness in Video Games: Exploratory Case Studies for Improving Interactive Depictions - Anderson, Sky LaRell (Loading, 2020)
This exploratory study examines three video games as case studies for how video games may portray mental illness through interactive, non-narrative design features. The analysis not only reports findings but also offers an evaluation for how video games might improve in how they depict mental illness. The games studied are What Remains of Edith Finch, Hellblade: Senua’s Sacrifice, and Doki Doki Literature Club. The analysis identifies how these games use audiovisual styles, control systems, game goals, and procedurality to portray mental illness. A report of the discovered themes precedes a discussion of innovations and weaknesses of those depictions of mental illness.